EFFECT OF NYPA FRUTICANS STEM AND LEAF EXTRACT ON GLUCOSE TOLERANCE IN GLUCOSE-INDUCED HYPERGLYCEMIC MICE - Reza, H.; Jahan, S.; Wahid, M.; Rahmatullah, M. M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Nypa fruticans (Thunb.) Wurmb. (Palmae), also known as Golpata in Bangladesh, is the only palm considered a mangrove. In this study, we examined the effect of methanol extract of stems and leaves on serum glucose lowering ability in glucose-induced hyperglycemic mice (glucose tolerance test). Fasted mice were divided into five groups. Group 1 (control) received distilled water. Groups 2-4 received methanol extract at oral doses of 100, 250 and 500 mg/kg body weight (bw). Group 5 received glibenclamide at an oral dose of 10 mg/kg bw. After 60 min of extract administration, the mice of all groups were orally treated with 2 g/kg bw of glucose. Blood samples were collected at 60 and 120 min after glucose loading and serum glucose levels determined. The significance of the results was calculated using Student’s t-test and were considered statistically significant when P<0.05. The methanol extract of Nypa fruticans did not demonstrate any significant lowering of serum glucose at 60 min. However, at 120 min after glucose loading, the extract demonstrated highly significant glucose lowering activity. At 120 min, the serum glucose levels of Groups 1-5 were respectively, 80.4 ± 2.4, 71.0 ± 0.6, 54.7± 2.6, 30.4 ± 2.4 and 59.5 ± 2.5 mg/dL (Mean ± SEM). The extract, when administered at 250 mg/kg bw demonstrated equivalent glucose lowering activity compared to the standard drug glibenclamide and at 500 mg/kg bw demonstrated